2020
DOI: 10.7759/cureus.10156
|View full text |Cite
|
Sign up to set email alerts
|

Remote Oncology Care: Review of Current Technology and Future Directions

Abstract: Cancer patients frequently develop tumor and treatment-related complications, leading to diminished quality of life, shortened survival, and overutilization of emergency department and hospital services. Outpatient oncology treatment has potential to leave cancer patients unmonitored for long periods while at risk of clinical deterioration which has been exaggerated during the COVID19 pandemic. Visits to cancer clinics and hospitals risk exposing immunocompromised patients to infectious complications. Remote p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Worldwide, many ePRO-symptom monitoring applications for cancer patients have been developed and tested in studies [ 5 , 49 , 50 ]. A recent rapid review showed mostly randomized trials and feasibility studies from Europe and North America to report these applications [ 5 ].…”
Section: Epro-symptom Monitoringmentioning
confidence: 99%
“…Worldwide, many ePRO-symptom monitoring applications for cancer patients have been developed and tested in studies [ 5 , 49 , 50 ]. A recent rapid review showed mostly randomized trials and feasibility studies from Europe and North America to report these applications [ 5 ].…”
Section: Epro-symptom Monitoringmentioning
confidence: 99%
“… 17 18 Following reSET, there are few other digital therapeutics products in the market already, and many more have been earning FDA approval consistently since 2017. 19 20 21 22 According to a previous study, in the United States, financial investment to promote the growth of a new business model in this field is actively occurring, which has tripled from about $1.5 billion in 2012 to $6 billion in 2017. There are about 320,000 health management mobile applications in the mobile app store, and this was double the number from 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, remote monitoring of electronic PROs, specifically cancer treatment–related symptoms, has been associated with improved quality of life and increased survival when providers intervene in response to worsening symptoms for the prevention of adverse downstream outcomes [ 41 ]. However, few studies in oncology have evaluated remote monitoring of biometric outcomes (eg, HS, temperature, blood pressure, weight, saturation of peripheral oxygen, and activity), with or without electronic PROs, using noninvasive digital technology [ 42 ]. In contrast, there has been greater progress in evaluating remote monitoring of biometric outcomes and PROs in respiratory, cardiovascular, and metabolic diseases and weight management [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from studies in chronic conditions other than cancer are consistent with ours; namely, the data feedback loop wherein remotely captured patient data are enacted upon by providers is critical to affecting patient health outcomes [ 43 ]. Patient engagement with remote monitoring, as reflected in adherence to use, may be a critical limitation with regard to the accuracy and fidelity of the collected data [ 42 ]. Thus, addressing the technological barriers identified in this study that may affect adherence may optimize the value of remote monitoring.…”
Section: Discussionmentioning
confidence: 99%